Reactive Oxidative Species in Carotid Body Chemoreception: Their Role in Oxygen Sensing and Cardiorespiratory Alterations Induced by Chronic Intermittent Hypoxia - Rodrigo Iturriaga; Hugo S. Diaz (Antioxidants, 2025)
The carotid body (CB) senses arterial PO2, PCO2, and pH levels, eliciting reflex responses to maintain cardiorespiratory homeostasis. Chronic intermittent hypoxia (CIH), the hallmark of obstructive sleep apnea, elicits autonomic and cardiorespiratory alterations that are attributed to an enhanced CB chemosensory responsiveness to hypoxia, which in turn activates neurons and glial cells in the nucleus of the tractus solitarius (NTS). Although the CB contribution to the CIH-induced pathological alterations is well-known, the underlying mechanisms are not fully understood. A growing body of new evidence suggests a crucial role for ROS in acute CB oxygen sensing, as well as in the potentiation of chemosensory discharge and the activation of the central chemoreflex pathway in CIH. Indeed, it has been proposed that acute hypoxia disrupts mitochondrial electron transport, increasing ROS and NADH in the chemoreceptor cells, which inhibit voltage-gated K+ channels, producing cell depolarization, Ca2+ entry, and release of excitatory transmitters. In addition, new evidence supports that the enhanced CB afferent discharge contributes to persistent CIH-induced cardiorespiratory alterations, likely triggering neuroinflammation in the NTS. Thus, in this review, we will examine the experimental evidence that supports the involvement of ROS in the acute O2 sensing process, and their role in the enhanced CB chemosensory discharges, the glial-related inflammation in the NTS, and the cardiorespiratory alterations induced by CIH.